ВПЛИВ ФІЗІОЛОГІЧНОГО СТАНУ КУЛЬТУРИ BRADYRHIZOBIUM JAPONICUM НА ЇЇ ЗДАТНІСТЬ ВСТУПАТИ У СИМБІОТИЧНІ ВІДНОСИНИ З РОСЛИНОЮ-ХАЗЯЇНОМ - Малиновська , І.М. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2007)
The influence ofphysiological state, cultivating and preservation terms of Bradyrhizobium japonicum 634б culture on its nodule activity and efficiency was studied. It was established, that maximum nodule mass is formed by plants, seeds of which are inoculated with the culture in good physiological condition, which has more incapsulated cell content and higher kinematics viscosity of cultural liquid; with the culture with cultivating term 5-10 days (when cultivated on agarized medium); with the quick-washed off culture; with the culture which passes less number of reseedings in the technological cycle in the conditions ofperiodical culture. The culture preservations on vermiculite is considered as one of the least effective.